Evaluating the use of recycled concrete aggregate and pozzolanic additives in fiber-reinforced pervious concrete with industrial and recycled fibers. (20th August 2020) - Toghroli, Ali; Mehrabi, Peyman; Shariati, Mahdi; Trung, Nguyen Thoi; Jahandari, Soheil; Rasekh, Haleh
Highlights: Concrete with RCA exhibited inferior mechanical strength, but higher permeability. SF and NC compensated the reduction in strength without any change in permeability. Waste plastic fiber can be recycled in previous concrete to enhance the strength. Combination of RCA, SF and NC affected dispersion of fibers, reduced effectiveness. Using 100% RCA with 2% STF and 2% NC set a 28-day compressive strength of 21 MPa. Abstract: The aim of this study is to investigate the effects of using recycled concrete aggregate (RCA) and pozzolanic materials as a partial replacement of natural coarse aggregate (NCA) and cement, respectively, on the mechanical and permeability properties of fiber-reinforced pervious concrete mixes. For this purpose, mixes were prepared with 25%, 50%, 75%, and 100% (by weight) RCA as coarse aggregate, and cement was partially replaced with 10% silica fume (SF) and 1%, 2%, and 3% nano-clay (NC). In order to enhance the mechanical strength of mixes, steel fiber (STF) and waste plastic fiber (WPF) were incorporated in the mixtures at a volume fraction of 1% and 2%. The experiments were carried out on a total number of 2310 samples casted from 110 mixes. Based on the test results, up to 25% increase in permeability and about 60% reduction in strength properties of mix incorporating 100% RCA were observed. The use of SF and NC led to enhancements in the strength properties because of micro-filling ability and pozzolanic reactivity. In general, the addition of fibers enhanced both compressive and flexural strengths up to 65% and 79%, respectively, over that of the unreinforced counterpart mix by incorporating 2% STF. WPF-reinforced mixes showed inferior performance compared to the STF-reinforced counterparts, due to the low quality and poor dispersion of WPF in mixes. It was found that, incorporating 100% RCA combined with 2% STF and 2% NC yields a pervious concrete suitable for structural applications.